A Critical Analysis of Artificial Intelligence Tools in Education: A Blessing or a Curse? - Mgala, Mvurya (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Clearly, the digital age is here with us, inevitably, Artificial Intelligence (AI) tools have penetrated the education sector with a promise to reshape the landscape of education. Among the many capabilities of AI tools is the promise to customize learning to individual needs, improve the laborious administrative tasks, and provide a deeper understanding of the student performance. However, this rapid adoption of AI tools into our education systems warrants a careful examination of both their transformative potential and the challenges they may pose. This paper provides a critical review of the implications of using AI tools in education, with the aim of weighing the benefits with the possible dangers that could result in the near future. This review looks at the extent of the integration of AI in education from basic to higher institutions of learning in the developed and developing world. It considers the possible benefits and potential pitfalls. Some of the concerns include the use of vast amounts of data since AI systems require vast amounts of data to function effectively. Further, there are issues of the possibility of over-dependence on AI tools which could hinder the development of critical thinking and socialization skills among students. The review also looks at the risk of possible worsening of the digital divide, as most students in the developing world do not have access to the latest technologies and infrastructure which could find themselves disadvantaged. This paper serves to motivate the development of a policy and guidelines that will can maximize the benefits of AI while minimizing risks in the adoption of AI tools in education. The paper is also motivates close collaboration among educators, technologists, and policymakers. This is important as we venture into the inevitable wave of AI also known as the Fourth Industrial Revolution.
Keywords: Artificial Intelligence; AI Tools, Digital divide, Personalized learning, AI algorithms, data security.